Active endothelin is an important vasoconstrictor in acute coronary thrombi - Adlbrecht, Christopher; Bonderman, Diana; Plass, Christian; Jakowitsch, Johannes; Beran, Gilbert; Sperker, Wolfgang; Siostrzonek, Peter; Glogar, Dietmar; Maurer, Gerald; Lang, Irene M. (Thrombosis and Haemostasis, 2007)
Acute coronary syndrome is characterized by compromised blood flow at the epicardial and microvascular levels. We have previously shown that thrombectomy in ST-elevation myocardial infarction (STEMI) accelerates ST-segment resolution, possibly by preventing distal embolization. We hypothesized that thrombus constituents contribute to microcirculatory dysfunction. Therefore, we analyzed the molecular and cellular composition of acute coronary thrombi, and correlated vasoconstrictive mediators with the magnitude of ST-segment resolution within one hour of percutaneous coronary intervention (PCI). Fresh coronary thrombi were retrieved in 35 consecutive STEMI patients who were treated with the X-Sizer thrombectomy catheter, and thrombus cell counts and vasoconstrictor concentrations were assessed. Twelve-lead ECG recordings were analyzed prior to and one hour after PCI. Concentration of endothelin (ET) was 20.0 (7.9–52.2) fmol/ml in thrombus compared with 0.1 (0.1–0.3) fmol/ml in corresponding peripheral plasma (p<0.0001), representing a selective 280 (70.0–510.0)- fold enrichment, exceeding enrichment of noradrenaline, angiotensin II and serotonin. Human coronary thrombus homogenates exerted vasoconstriction of porcine coronary artery rings that was inhibited by the dual ET receptor blocker tezosentan. Extracted ET (r=0.523 p=0.026) and number of leukocytes (r=0.555 p=0.017) were correlated with the magnitude of STsegment resolution. In conclusion, the amount of active ET and white blood cells aspirated from STEMI target vessels correlated with improvement of territorial microcirculatory function as illustrated by enhanced ST-segment resolution.
Keywords: Acute myocardial infarction; thrombosis; endothelin / -receptors; leukocyte function / activation; arterial thrombosis